2022
DOI: 10.3390/genes13112009
|View full text |Cite
|
Sign up to set email alerts
|

A Pilot Study on the Prediction of Non-Contact Muscle Injuries Based on ACTN3 R577X and ACE I/D Polymorphisms in Professional Soccer Athletes

Abstract: Muscle injuries are among the main reasons for medical leavings of soccer athletes, being a major concern within professional teams and their prevention associated with sport success. Several factors are associated with a greater predisposition to injury, and genetic background is increasingly being investigated. The aim of this study was to analyze whether ACTN3 R577X and ACE I/D polymorphisms are predictors of the incidence and severity of muscle injury in professional soccer athletes from Brazil, individual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1
1

Relationship

3
2

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 55 publications
7
6
0
Order By: Relevance
“…Regarding the ACE I/D polymorphism, the present study supports previous ndings that showed the protective effect of the D-allele against muscle injuries [5,21] and muscle damage. More in detail, de Almeida et al [21] recently showed that Brazilian professional football players with the ACE II genotype had almost 2 fold the number of injuries per season compared to those with the ID + DD genotypes (p = 0.03).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Regarding the ACE I/D polymorphism, the present study supports previous ndings that showed the protective effect of the D-allele against muscle injuries [5,21] and muscle damage. More in detail, de Almeida et al [21] recently showed that Brazilian professional football players with the ACE II genotype had almost 2 fold the number of injuries per season compared to those with the ID + DD genotypes (p = 0.03).…”
Section: Discussionsupporting
confidence: 91%
“…Regarding the ACTN3 polymorphism, our results support previous ndings that showed the protective effect of the Rallele against muscle injuries [4,21] and muscle damage. According to a recent systematic review, athletes with the ACTN3 XX genotype may be more likely to sustain certain non-contact injuries, such as muscle damage, ankle sprains, and higher levels of exercise-induced muscle damage, which could hurt injury frequency and severity in comparison to RX and RR genotypes [27].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Generally, low ROM is known to increase the risk of muscle injury [42][43][44]. However, the X allele of ACTN3 R577X polymorphism has a higher ROM than the RR genotype and a higher risk of muscle injury [13][14][15]. A previous study suggested that the X allele had higher muscle damage such as creatine kinase activity and muscle soreness compared to the RR genotype [45].…”
Section: Discussionmentioning
confidence: 99%
“…ACTN3 R577X polymorphism influences muscle strength [9] and power/sprint athletic status [10]. Because deficiency of α-actinin-3 alters muscle structure, the ACTN3 R577X polymorphism is associated with muscle damage [11,12] and muscle injury [13][14][15]. ACTN3 R577X polymorphism, which regulates α-actinin-3 expression, influences not only muscle contractile properties such as muscle strength and power but also flexibility.…”
Section: Introductionmentioning
confidence: 99%